Antitumor Effects of Astaxanthin on Esophageal Squamous Cell Carcinoma by up-Regulation of PPARγ. (21st April 2022) - Cui, Lingling; Li, Zhonglei; Xu, Fan; Tian, Yalan; Chen, Tingting; Li, Jiaxin; Guo, Yingying; Lyu, Quanjun
Abstract: Esophageal squamous cell carcinoma is a malignant tumor that is difficult to find and has a poor prognosis. The aim of this study is to explore the chemoprevention effect of Astaxanthin (AST) and reveal the possible mechanism of AST on the development of esophageal cancer based on PPARγ. We found that a stable and strong binding between PPARγ molecules and AST molecules using Autodock 4.0 software. AST significantly inhibited the viability of EC109 cells in a dose and time dependent manners (all P < 0.05), and up-regulated the protein expression level of PPARγ from the concentration of 6.25 µM ( P < 0.05). Animal experiment showed that AST significantly decreased the incidences of NMBzA-induced esophageal carcinogenesis at 50 mg/kg AST in F344 rats ( P < 0.05). AST inhibited the oxidative stress by improving the levels of superoxide dismutase (SOD), total antioxidant capacity (TAOC) and suppressing malondialdehyde (MDA) in serum, and increasing the protein of PPARγ, Bax/Bcl-2, Caspase-3 in esophagus tissue, especially in the 50 mg/kg of AST intervention group (all P < 0.05). In conclusion, our data suggested that protective effect of AST on esophageal cancer by inhibiting oxidative stress, up-regulating PPARγ, and activating the apoptotic pathway, which could provide a basis for clinical application of AST.